2015
DOI: 10.1007/s10858-014-9892-5
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of the G protein-coupled neuropeptide Y2 receptor in monounsaturated membranes investigated by solid-state NMR spectroscopy

Abstract: In contrast to the static snapshots provided by protein crystallography, G protein-coupled receptors constitute a group of proteins with highly dynamic properties, which are required in the receptors' function as signaling molecule. Here, the human neuropeptide Y2 receptor was reconstituted into a model membrane composed of monounsaturated phospholipids and solid-state NMR was used to characterize its dynamics. Qualitative static (15)N NMR spectra and quantitative determination of (1)H-(13)C order parameters t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 61 publications
1
35
0
1
Order By: Relevance
“…Axially symmetric rotational diffusion of the membrane protein is manifested by anisotropic lineshapes indicative of axially symmetric chemical shift anisotropy tensors (η = 0). Superimposed to these broad lineshapes, large amplitude motions give rise to very narrow lines detected at the isotropic chemical shift of the respective resonances2224. However, as static 15 N NMR spectra are almost always acquired using cross polarization (CP), the recorded spectra show a strong bias towards rigid structures and dynamic features are only detected if sufficiently long CP contact times are used24.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Axially symmetric rotational diffusion of the membrane protein is manifested by anisotropic lineshapes indicative of axially symmetric chemical shift anisotropy tensors (η = 0). Superimposed to these broad lineshapes, large amplitude motions give rise to very narrow lines detected at the isotropic chemical shift of the respective resonances2224. However, as static 15 N NMR spectra are almost always acquired using cross polarization (CP), the recorded spectra show a strong bias towards rigid structures and dynamic features are only detected if sufficiently long CP contact times are used24.…”
Section: Resultsmentioning
confidence: 99%
“…This observation indicates that in addition to the axially symmetric rotational diffusion of the GHS receptor in the membrane, significant portions of the molecule also undergo large amplitude motions. We have previously quantified the proportion of highly mobile segments of the Y 2 receptor by acquiring static 15 N NMR spectra as a function of CP contact time as well as directly excited 15 N NMR spectra24. It could be shown that static 15 N CP spectra recorded at a CP contact time of 8 ms can be readily quantified to provide the relative proportion of relatively rigid and highly mobile residues24.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing number of interesting dynamics studies that address proteins of increasing complexity and biological interest, such as membrane proteins [104,184,185] and amyloid fibrils [106,186,187]. For reasons of limited space we focus here only on one particular aspect of biomolecular dynamics.…”
Section: Selected Examples Of Recent Applications: How Do Protein Motmentioning
confidence: 99%
“…As opposed to being passive connectors, the loops and other inter-helix segments could assume added importance for establishing the conformations and regulating the functions of prominent classes of membrane proteins such as, for example, the seven-helix G-protein-coupled receptors [3132] . It has been observed, for example, that helix fraying is a mechanism by which multi-span proteins such as G-protein-coupled receptors may adjust to a decrease in the hydrophobic thickness of the surrounding membrane [3334] .…”
mentioning
confidence: 99%